(untitled) (Gestión y Gerencia, 2024)
The purpose of this essay is to explore the importance of continuous adaptation as a key element of the "DNA" of ambidextrous organizations, that is, those that balance the exploitation of their existing capabilities with the exploration of new opportunities. The main results and conclusions highlight that continuous adaptation enables ambidextrous organizations to remain relevant and competitive in volatile and changing business environments. This involves fostering a culture of experimentation and learning, promoting collaboration and open communication, and investing in technology and agile processes. Additionally, the crucial role of leadership in developing this adaptive capacity as a fundamental part of organizational DNA is emphasized. Finally, the connection between continuous adaptation and business sustainability is established, as the former fosters resilience, innovation, and social responsibility, key elements for ensuring the long-term viability of organizations in an increasingly complex environment.